Rapid Antigen Tests For Safe School Opening in the COVID-19 Pandemic Era. Issue 8 (13th July 2022) - Goldenfeld, Miki; Cohen, Carmit; Gilboa, Mayan; Pessach, Itai M.; Mehnick, Bella; Tal, Ilana; Meltzer, Lilac; Amit, Sharon; Gonen, Tal; Afek, Arnon; Kreiss, Yitshak; Regev-Yochay, Gili
Abstract : Background: Since the beginning of the Sever Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic, school closure as a mitigating measure was at the center of a public and professional debate. While the negative effects of school closure cannot be ignored, accumulating data suggested that it is necessary for reducing community transmission. Our study presents an optional strategy for safe school opening during a pandemic, implemented in selected Israeli high schools by a special task force constructed by the Sheba Medical Center (SMC). Methods: The study took place between November 2020 and April 2021. Three schools from different areas of Israel were enrolled. The participants were asked to undergo bi-weekly SARS-CoV-2 rapid diagnostic antigen tests (Ag-RDT). Those who tested positive were requested to self-isolate, whereas their school contacts were tested daily by Ag-RDT. Participants with a previously documented SARS-CoV-2 infection or who were found to be SARS-CoV-2 seropositive upon enrollment were exempted from screening. Results: Of a total of 361 participants who enrolled in the study, 12.3% were found to be seropositive. Fourteen SARS-CoV-2 cases were detected (3.5%), 12 of them in one single school located in an endemic area for SARS-CoV-2. The 14 cases resulted in 84 days of COVID-19-related absence from school, comparing with 1775 potential days of COVID-19-related absence under a strategy implementing self-isolation instead of testing. Conclusions: Safe continuation of academic routine during the pandemic is possible when using rapid Ag-RDT as a screening tool, while allowing swab collection by trained students and teachers.